(untitled) (Nóema, 2020)
This paper explores Whitehead’s concept of law as an immanent order, arguing that it can be successfully used to cover the whole semantic field denoted as ‘law’, and especially law in its juridical sense. After showing the features that make it more plausible and more desirable than the opposing view of law as a transcendent imposition, law will be defined as the expression of the modes of existence of individuals within their environment. It will then be tested as a key for understanding the link between life and law and showing the inadequacy of Foucault and Agamben’s biopolitical reflections: if law is an immanent order, then life is identical with its own inherent normativity. Finally, drawing on Deleuze’s philosophy of right, the fundamental features of an immanent practice of law, a “speculative jurisprudence” which confirms the binding between law, life, and immanence, will be sketched as a proposal for a practical philosophy consistent with Whitehead’s process cosmology.